Characterization of Anopheles gambiae (African Malaria Mosquito) Ferritin and the Effect of Iron on Intracellular Localization in Mosquito Cells. Issue 1 (13th June 2015) - Geiser, Dawn L.; Conley, Zachary R.; Elliott, Jamie L.; Mayo, Jonathan J.; Winzerling, Joy J.
Abstract : Ferritin is a 24-subunit molecule, made up of heavy chain (HC) and light chain (LC) subunits, which stores and controls the release of dietary iron in mammals, plants, and insects. In mosquitoes, dietary iron taken in a bloodmeal is stored inside ferritin. Our previous work has demonstrated the transport of dietary iron to the ovaries via ferritin during oogenesis. We evaluated the localization of ferritin subunits inside CCL-125 [ Aedes aegypti Linnaeus (Diptera: Culicidae), yellow fever mosquito] and 4a3b [ Anopheles gambiae Giles (Diptera: Culicidae), African malaria mosquito] cells under various iron treatment conditions to further elucidate the regulation of iron metabolism in these important disease vectors and to observe the dynamics of the intracellular ferritin subunits following iron administration. Deconvolution microscopy captured 3D fluorescent images of iron-treated mosquito cells to visualize the ferritin HC and LC homologue subunits (HCH and LCH, respectively) in multiple focal planes. Fluorescent probes were used to illuminate cell organelles (i.e., Golgi apparatus, lysosomes, and nuclei) while secondary probes for specific ferritin subunits demonstrated abundance and co-localization within organelles. These images will help to develop a model for the biochemical regulation of ferritin under conditions of iron exposure, and to advance novel hypotheses for the crucial role of iron in mosquito vectors.